Philippine Normal University: interactive kiosk. - Guerrero, Kevin C. (2013)
The Philippine Normal University Information Kiosk is a system which was developed in order to provide guidance and information about the details of the university towards the users (e.g. Visitors, Students, faculty members etc.). In our generation today, interactivity with computer and other technology, in regards with gathering information, is essential to daily life. Information Kiosks are mainly used for detailing information to users via interactive touch screen and other visually appealing designs. The proponents’ proposed system was an Information Kiosk developed for the Philippine Normal University is a type of information kiosk which mainly focuses on providing a digital map of the University (or the insides of an establishment if it was for a company) and giving detailed information in regards with the background of the University and its buildings. A digital map of the University is present within the kiosk and can be used to search for the shortest possible path in finding the user’s desired location. The developed Information Kiosk not only provides the shortest path to the user but it also shows the academic calendar of the University and its upcoming events.